Narratives of a third generation Mexican-American family in northern Colorado - Hawthorne, Barbara L., author; Banning, James H., advisor; Davies, Timothy Gray, advisor; Theodoratus, Robert, committee member; Bohren, Lenora, committee member (Colorado State University. Libraries, 2004)
This dissertation is a study of one Mexican-American family over time in the context of the larger Mexican-American and Anglo-American communities in northeastern Colorado. The research is a continuation of a previous study that focused upon the first and second generations of this particular family, who originally came to Colorado around 1920 in search of employment opportunities and in hopes of improved styles of living. From this sample family, the study seeks an understanding of the changes in the personality profile of the larger Mexican-American community. This study differs from other cultural and historical studies in that it utilized oral narratives and visual stories as the primary data resources. This is the first in-depth study of this type for the Mexican-American population in northeastern Colorado, specifically in the South Platte River Valley of Larimer and Weld counties. Besides the presentation of a complex story of a particular immigrant family over time and place, a persistent challenge has decorated this study: to integrate anthropological and educational theory and methodology with a narrative and visual approach to cultural ethnography. This type of interdisciplinary approach involved a social process of mutual orientation and exchange developed in interactive dialogue. Through this interactive exchange oral and visual narratives emerged that represented how each family member perceived and interpreted past experiences in meaningful contexts, today. This study began in Mexico and followed Hinojos and Carmelita from northern Mexico to the fields of northeastern Colorado, and further accompanied their children, the second generation into the urban barrios where they were initially exposed and immersed into the dominant Anglo arena. Family members of the second generation told stories about poverty, education, new jobs and residencies. As adults, some moved away from family and neighborhoods and, thus, from traditional ties to suburban communities. Others remained in the ethnic neighborhood. All family members, however, changed and represented a diversified personality profile for the second generation. Finally, this study attempted to understand the variability of the third generation. In spite of the transformations that resulted in their increased exposure and immersion into the dominant Anglo community, the third generation Mexican-American family emerged on a foundation strengthened by origins and traditions in Mexico, and by the dynamics of adaptability over time and place. The result of this research was a revealing profile of the cultural evolutions that took place over three generations in two counties of northern Colorado, Larimer and Weld, a region that experienced a Mexican-American population who originally were isolated residing near their work in the fields to one that, over time, moved to urban neighborhoods and eventually became embedded in the dominant Anglo cultural arena. In this evolutionary process it was the second generation who were torn between tradition and new ways of thinking and behaving, between poverty and economic mobility, and between marginalization and acculturation. It was the third generation who in the process of acculturation had limited or no access to traditional knowledge funds and found this not important or relevant, or chose to create a "folk culture" based on what knowledge they did have with that which was imagined. A specific objective of this study was to distinguish the Mexican-American story in this geographical area from other stories in Colorado. Research questions asked if the third generation represented a unique cultural profile, and if so, what factors contributed to the changes across generations? The data from this research revealed an evolutionary personality profile for the third generation family members. Although many aspects of the previous generations prevailed, more had changed. In a proposed inductive style, stories emerged to explain the reasons for changes in interpretation and meanings across generations. What was important for second generation family members no longer had significant meaning for the third generation, in this sense, a distinction can be made across generations but one that is blurred by individual differences, settlement patterns, socioeconomic status, educational levels, changing world views, and the adaptation to and adoption of dominant Anglo styles of living, ideologically and behaviorally. In essence, it can be suggested that the second generation was more unique to northern Colorado than the third. The blending into a more universal "American" profile by third generation family members proposed a less geographically-based one. It is not unreasonable to emphasize that the Mexican-American population comprises an integral part of Colorado's historical panorama and presently is expanding into a dominant population factor for northern Colorado. It is becoming imperative that public institutions recognize the dynamic demographics in northern Colorado and realize that in order to respond to growing needs they will need to understand increasing ethnic diversity. Hopefully, this study will provide a framework and some much needed data in order to help understand the larger picture, as well as provide a basis for future research.
Keywords: cultural anthropology; Colorado history; multicultural education